If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 = n + -18 Reorder the terms: 18 = -18 + n Solving 18 = -18 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 18 + -1n = -18 + n + -1n Combine like terms: n + -1n = 0 18 + -1n = -18 + 0 18 + -1n = -18 Add '-18' to each side of the equation. 18 + -18 + -1n = -18 + -18 Combine like terms: 18 + -18 = 0 0 + -1n = -18 + -18 -1n = -18 + -18 Combine like terms: -18 + -18 = -36 -1n = -36 Divide each side by '-1'. n = 36 Simplifying n = 36
| x=2/64 | | 24x+25x=8 | | (2*x)+(6*y)=72 | | 3x-8x-5=-4 | | 2x^2/(0.07-x)^2=49 | | x+5(x-1)=11 | | 2x-x=x-2 | | f(2)=x^2 | | f(0)=x^2 | | f(x)=4-11 | | 7=2x/(.07-x) | | 4x-2/3y=8 | | 4x-0.6y=8 | | 3=2+2/z+2 | | 9m-3=6m+m+6+3 | | 5x+12=7x-44 | | 6+4x=9x-34 | | 4x-7(x-2)=3(7-x) | | 2n+1=1 | | ln(3x)=-x+2 | | 60+0.5x=120+0.35y | | 3+2n+6+n+3+n= | | 4(n+2)=5(n-3) | | X(0.3)=14500+Y | | y=18(c+1)-2 | | y-2(-1)=0 | | 3(z+2)-4z= | | 3x-(4x-8)=9x-12 | | |x/2|=2 | | 4a+5b-9a+6ab-11b= | | (-2.5x^3)(5x^2)= | | 18q-2=18c+16 |